“Winning could mean success, yet losing doesn’t mean failure”—Using a mobile serious game to facilitate science learning in middle school - Liu, Sa; Grey, Brian; Gabriel, Mina (Frontiers in Education, 2023)
Researchers have recognized the potential of using Mobile Serious Games (MSG) in teaching various subject matters. However, it is not clear how MSG impacts students differently based on their in-game performance. To fill this gap, the current study examined the MSG “SpacEscape” that teaches middle school students about the solar system through problem-solving activities. To understand whether SpacEscape could facilitate middle school student science learning based on their in-game performance, this study adopted a randomized experimental design and collected pre-test, post-test and game play data from the participants. Independent sample t-test and MANOVA with repeated measures (N = 228) were conducted. The results showed that SpacEscape significantly improved science learning for middle school students. In addition, the game significantly improved students’ science knowledge test scores regardless of their in-game performance. Furthermore, students enjoyed playing SpacEscape in the class, and we hope this study will inform the direction of future study in the field.